Analysing tourism attractiveness using probabilistic travel model: a study of Gangtok and its surroundings - Paul, Suman (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Eco-tourism is now one of the largest industries in the world. Gangtok as a core centre of Sikkim commands over different tourist spots in East Sikkim which are directly linked by a network of roads centering Gangtok and are perfectly accessible for one-day trips. The tourist attractions of East Sikkim are clustered mostly in and around Gangtok, the state capital. This study analyses the tourism infrastructure as well as seasonal arrival of tourists in the Gangtok city and develop a probabilistic travel model on the basis of tourist perception which will help the tourism department to further the economic development of the area.